Pengaruh Peran Petugas Lapang Terhadap Partisipasi Petani Dalam Pengembangan Model Desa Kakao Di Kabupaten Gunungkidul - Kurnia Tanjungsari; Sunarru Samsi Hariadi; Endang Sulastri (Agro Ekonomi, 2016)
The development of cocoa village model are activities that make the region an area of cocoa as a pilot model by optimizing cultivation (on farm), and post harvest processing (off farm), and the strengthening of human and institutional resources. This activity has a principle of the active participation of farmers. In order for farmers to have an active participation in the development of the model village of cocoa required field officers role as a communicator, motivator, organizer, facilitator, and consultant. The research aimed to find out the influence of the role of field officers on the Farmer Participation in The Development of Cocoa Village Model in Gunungkidul. The basic method of research was descriptive analysis with quantitative approach. The research took place purposively at 4 groups of farmers in Patuk Subdistrict, Gunungkidul with the consideration that the programs was only done at the site. 120 samples was taken by simple random sampling method as respondents were used and then the data analyzed with simple linear regression. The results showed that the role of field officers affected the farmers’ participation in the program, which means increasingly frequent field officers carry out its role, the participation of farmers will be increased so that the role of field officers need to be optimized especially role as a motivator.